Neodymium-iron-boron sintering method beneficial to decarburization

By adopting a multi-stage heating and insulation platform during the NdFeB sintering process, and inert gas is introduced and extracted during insulation to form an alternate insulation sintering of inert gas pressure differential, the problem of difficulty in removing carbon elements in NdFeB sintering is solved, and the magnetic properties of the magnet are improved.

CN119889855AActive Publication Date: 2025-04-25NINGBO YUNSHENG CO LTD +1
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202510371001.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-27
Publication Date
2025-04-25
Estimated Expiration
2045-03-27

AI Technical Summary

Technical Problem

During the sintering process of neodymium iron boron, it is difficult to effectively remove carbon elements, which affects the performance of the matrix and the smooth flow of grain boundary diffusion channels.

Method used

A multi-stage heating and insulation platform is used to pass in and extract inert gas during insulation to form an alternate insulation and sintering of inert gas pressure difference to reduce the internal carbon content of the blank.

Benefits of technology

Through this method, the carbon content inside the blank is effectively reduced, the smoothness of grain boundary diffusion channels are improved, and the magnetic properties of neodymium iron boron magnets are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119889855A_ABST
    Figure CN119889855A_ABST
Patent Text Reader

Abstract

The chemical formula of a neodymium-iron-boron magnet is RX1T (100-X1-X2-X3-X4) MX3AX4BX2, and the neodymium-iron-boron magnet sintering method mainly comprises the following steps that neodymium-iron-boron raw materials are mixed in proportion, smelted into alloy liquid, cast into cast pieces and ground into powder, the powder is put into a tank with inert gas protection and fully stirred, the powder is pressed into a blank and subjected to orientation forming, and the neodymium-iron-boron magnet is obtained. According to the method, vacuum packaging, water isostatic pressing and sintering and film stripping are adopted, a multi-stage heat preservation and temperature rise mode is adopted for sintering, inert gas is introduced and extracted during heat preservation to form inert gas pressure difference alternate heat preservation sintering, after sintering is completed, cooling is conducted to the temperature below 100 DEG C, the center of a sintered magnet is taken, and the content of nitrogen, oxygen and carbon in a blank is tested. According to the neodymium iron boron sintering method beneficial to decarburization, in the neodymium iron boron sintering process, the carbon element is removed through the sintering technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of NdFeB production, in particular to a NdFeB sintering method which is helpful for decarburization. Background Art

[0002] With the rapid development of rare earth permanent magnet applications, the demand for high-performance and low-cost NdFeB permanent magnets has increased rapidly. Therefore, improving the magnetic properties of NdFeB and developing high-performance sintered NdFeB have become the primary technical challenges. One of the main applications of rare earth permanent magnet materials is to manufacture various permanent magnet motors. Compared with traditional motors, permanent magnet motors have the characteristics of light weight, small size, high efficiency and energy saving, and strong reliability. Sintered NdFeB permanent magnets are small in size and high in performance, which can well reduce the mass of motors and improve motor efficiency, and are more suitable for miniaturization and lightweighting of automobiles.

[0003] At present, the coercivity (H CJ The most effective method is to use heavy rare earth elements terbium (Tb) and dysprosium (Dy) to replace the neodymium (Nd) element in the alloy to form (Nd,Tb)2Fe 14 B or (Nd,Dy)2Fe 14 B. Among them, grain boundary diffusion technology and grain boundary doping technology are effective ways to prepare heavy rare earth-free or low heavy rare earth high coercivity materials.

[0004] Once the grain boundary diffusion technology was proposed, it attracted widespread attention in the industry and has been rapidly industrialized in recent years. In actual industrial production, the use of the grain boundary diffusion process can reduce the consumption of heavy rare earth by more than 50%. However, the grain boundary diffusion process has higher requirements for the blank matrix. The lower the carbon, oxygen and nitrogen content in the matrix, the easier it is to ensure smooth passage of grain boundary diffusion.

[0005] For the matrix of grain boundary diffusion, the introduction of carbon elements is intentionally reduced as much as possible during the powder making and molding stages, such as reducing the use of lubricants and surface modifiers. However, for the flow and molding of the powder, it is inevitable to add antioxidants, air flow mill protective agents, etc. Therefore, the unavoidable introduction of this part of carbon elements affects the performance of the matrix while also affecting the smoothness of the grain boundary diffusion channel. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a NdFeB sintering method which is helpful for decarburization and can remove carbon element by using a sintering process during the NdFeB sintering process.

[0007] The technical solution adopted by the present invention to solve the above problems is: a sintering method of NdFeB that is conducive to decarburization, the chemical formula of NdFeB magnet is R X1 T (100-X1-X2-X3-X4) M X3 A X4 BX2 During sintering, a multi-stage heating and insulation platform is used, and during insulation, inert gas is introduced and extracted to form an inert gas pressure difference for alternating insulation sintering, thereby reducing the carbon content inside the blank. The steps are as follows: S1: Mix NdFeB raw materials in proportion; S2: Smelting the NdFeB raw materials into alloy liquid; S3: Casting the alloy liquid into casting sheets; S4: Grind the casting flakes into powder, put them into a tank protected by inert gas, and stir them thoroughly; S5: Pressing the powder into a green compact and orienting the green compact; S6: vacuum packaging; S7: performing water isostatic pressing; S8: Sintering and film stripping are performed. The sintering adopts a multi-stage heat preservation and temperature rise form, and inert gas is introduced and extracted during the heat preservation to form an inert gas pressure difference for alternating heat preservation and sintering; S9: After sintering, high-purity inert gas is filled in to cool down to below 100°C; S10: Take the center part of the sintered magnet and test the nitrogen and oxygen contents in the blank by pulse infrared absorption method, and test the carbon content in the blank by high-frequency-infrared absorption method.

[0008] Compared with the prior art, the advantages of the present invention are: through step S8, during the sintering process, staged insulation is adopted to avoid the formation of a high-temperature reaction isolation layer, ensuring that the temperature inside and outside the blank is consistent, thereby ensuring that the diffusion channel is open; at the same time, the inert gas pressure difference in the insulation section is alternately adopted to promote the interaction between the organic gas and the inert gas, and then a vacuum pump is used to form a negative pressure to take away more carbides.

[0009] As an improvement of the present invention, in step S8, the following steps are included: S8.1: Start heating from room temperature; S8.2: Raise the temperature to 100°C~400°C; S8.3: Keep warm for 1h~4h; S8.4: Raise the temperature to 400°C~600°C; S8.5: Keep warm for 1h~4h; S8.6: Raise the temperature to 600°C~900°C; S8.7: Keep warm for 1h~4h; Through the improvement, in conventional sintered NdFeB materials, organic matter adsorbed on the surface of the blank, such as release agents, can be vaporized at 100°C-400°C and discharged from the blank along the diffusion channel, so a long first preheating is performed in S8.2 and S8.3; then the temperature is raised again through steps S8.4 and S8.5. At this stage, the gaps between particles in the blank are further reduced, and hydrogen, carbon, and oxygen-containing substances with strong bonds with the powder particles escape; then, through steps S8.6 and S8.7, the temperature is raised by 600°C to 900°C, and liquid phase begins to appear in the sintered NdFeB, the particles are rearranged, and the diffusion channel becomes narrower. This stage requires a long time to reach the lowest temperature gradient inside and outside the blank, eliminating the phenomenon that the channel is blocked due to the high temperature and more liquid phase outside the blank, so that the organic matter cannot be discharged.

[0010] As an improvement of the present invention, steps S8.3, S8.5 and S8.7 all include the following steps: A1: After starting to keep warm, fill with inert gas; A2: After keeping it for a while, vacuumize it; A3: After maintaining the vacuum state for a period of time; A4: Repeat steps A1-A3 at least twice; Through the improvement, during the sintering process, the carbon element removed from the blank is mainly directly volatilized or formed into carbide gas. Therefore, through steps A1-A4, the mobility of the volatile carbon and carbide gas can be enhanced, and sufficient diffusion time can be provided to allow it to quickly diffuse into the entire sintering equipment. Then, by filling inert gas, the volatile carbon and carbide gas are diluted, so that the volatile carbon and carbide gas can be fully diffused into the inert gas. When vacuuming is performed, the difficulty of extracting the volatile carbon and carbide gas is reduced, thereby reducing the inhibitory effect of the volatile carbon and carbide gas on the subsequent decarburization reaction.

[0011] Through the improvement, after step S8.7, the method further comprises step S8.8: evacuating the vacuum to a vacuum degree less than 10 -2 Pa, the sintering temperature is raised to 1050±50°C, and the heat preservation time is 4 to 15 hours. Through the improvement, the blank is sintered and shaped.

[0012] As an improvement of the present invention, in step S9, after sintering is completed, high-purity inert gas is filled in to cool to below 100°C. Through the improvement, after the blank is sintered and formed in a vacuum, by filling with high-purity inert gas, not only can the blank be quickly cooled, but also cooled to below 100°C, thereby ensuring that the blank after sintering tends to a stable state and ensuring the sintering quality of the blank.

[0013] As an improvement of the present invention, after step S9, the method further includes step S9.1: performing aging treatment on the sintered magnet. Through the improvement, the magnetic properties of the magnet are enhanced through aging treatment.

[0014] As an improvement of the present invention, in step S4, step S4.1 is included: adding a powder modifier, the addition ratio is 0.05wt%-0.5wt%, and the powder is fully stirred. Through the improvement, the anti-oxidation protection effect can isolate the magnetic powder from contact with the air, and the oxidation risk of the NdFeB powder before sintering can be significantly reduced; the powder fluidity is improved, and the lipophilic hydrocarbon chain structure of the modifier can reduce the force between the powder particles, inhibit agglomeration, and make the powder easier to flow and evenly fill the mold; enhance flame retardancy and safety. In the processing links such as air flow milling, the modifier reduces the surface activity of the powder to prevent the magnetic powder from causing combustion accidents due to friction or collision; promote magnetic field orientation. The lubricating effect of the modifier makes it easier for the magnetic powder particles to rotate in the magnetic field and have a consistent orientation, thereby improving the remanence B of the magnet. r and maximum energy product (BH) max .

[0015] As an improvement of the present invention, step S5 includes step S5.1: spraying a demoulding agent during the molding process. The improvement facilitates demoulding of the blank after molding.

[0016] As an improvement of the present invention, the following steps are also included: S11: processing the sintered magnet into thin sheets and performing grain boundary diffusion; S12: Using a magnetic tester to test the magnetic properties before and after diffusion, through the improvement, the sintered magnet is subjected to grain boundary diffusion to further improve the magnetic properties of the magnet, and then the change in the magnetic properties is measured. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 It is a schematic diagram of the sintering curve of the present invention and the pressure change curve of the sintering equipment. DETAILED DESCRIPTION

[0018] The embodiments of the present invention are further described below in conjunction with the accompanying drawings.

[0019] A sintering method of NdFeB magnets that helps decarburization. The chemical formula of NdFeB magnets is R X1 T (100-X1-X2-X3-X4) M X3 A X4 B X2 ; Where X1, X2, X3 and X4 are the mass percentages of the corresponding elements respectively; R is selected from one or more rare earth elements, 28.5wt%≤X1≤32.5wt%; T is selected from Fe and Co, the content of Co is 0-1.0wt%, and the balance is Fe; M is selected from one or more of Ti, Zr and Nb, 0.1wt%≤X3≤0.35wt%; A is selected from Cu, Ga and Al, 0.0wt%≤X4≤1.2wt%; B is B, and its content is 0.88wt%≤X2≤0.98wt%; During sintering, a multi-stage heating and insulation platform is used, and during insulation, inert gas is introduced and extracted to form an inert gas pressure difference for alternate insulation sintering, thereby reducing the carbon content inside the blank. The steps are as follows: S1: Mix NdFeB raw materials in proportion; S2: Smelting the NdFeB raw materials into alloy liquid; S3: Casting the alloy liquid into casting sheets; S4: Grind the casting flakes into powder, put them into a tank with inert gas protection, and stir them thoroughly; S4.1: Add powder modifier at a ratio of 0.05wt%-0.5wt% and stir thoroughly; S5: Pressing the powder into a green compact and orienting the green compact; S5.1: Spraying release agent during molding; S6: vacuum packaging; S7: performing water isostatic pressing; S8: Sintering and film stripping are performed. The sintering adopts a multi-stage heat preservation and temperature rise form, and inert gas is introduced and extracted during the heat preservation to form an inert gas pressure difference for alternating heat preservation and sintering; S8.1: Start heating from room temperature; S8.2: Raise the temperature to 100°C~400°C; S8.3: Keep warm for 1h~4h; S8.3.1: Fill with inert gas; S8.3.2: After holding for a period of time, apply vacuum; S8.3.3: After a period of time under vacuum; S8.3.4: Repeat S8.3.1-S8.3.3 not less than once. S8.4: Raise the temperature to 400°C~600°C; S8.5: Keep warm for 1h~4h; S8.5.1: Fill with inert gas; S8.5.2: After holding for a period of time, apply vacuum; S8.5.3: After a period of time under vacuum; S8.5.4: Repeat S8.5.1-S8.5.3 not less than once. S8.6: Raise the temperature to 600°C~900°C; S8.7: Keep warm for 1h~4h; S8.7.1: Fill with inert gas; S8.7.2: After holding for a period of time, apply vacuum; S8.7.3: After a period of time under vacuum; S8.7.4: Repeat S8.7.1-S8.7.3 not less than once. S8.8: Evacuate to a vacuum degree less than 10 -2 Pa, the sintering temperature is raised to 1050±50℃, and the heat preservation time is 4 to 15 hours; S9: After sintering, high-purity inert gas is filled in to cool down to below 100°C; S9.1: Perform aging treatment on the sintered magnet; S10: taking the center part of the sintered magnet, testing the nitrogen and oxygen contents in the blank by pulse infrared absorption method, and testing the carbon content in the blank by high frequency-infrared absorption method; S11: The sintered magnet is processed into a 10 mm × 10 mm × 5 mm thin sheet and subjected to grain boundary diffusion; S12: The magnetic properties before and after diffusion are tested using a NIM62000 magnetic tester.

[0020] Example 1.1: The casting formula is: (PrNd) 30% B 0.94% Ti 0.2% (Al + Cu + Ga) 0.35% Co 1%, and the rest is Fe.

[0021] The steps are as follows: S1: Mix NdFeB raw materials in proportion; S2: Smelting the NdFeB raw materials into alloy liquid; S3: Casting the alloy liquid into casting sheets; S4: Grind the casting flakes into powder, put them into a tank protected by inert gas, and stir them thoroughly; S4.1: Add powder modifier at a ratio of 0.1wt% and stir thoroughly; S5: Pressing the powder into a green compact and orienting the green compact; S5.1: During the molding process, a release agent is sprayed in, with a weight ratio of 0.1wt%; S6: vacuum packaging; S7: performing water isostatic pressing; S8: Sintering and film stripping are performed, and the sintering adopts a multi-stage heat preservation and heating form; S8.1: Start heating from room temperature; S8.2: Raise the temperature to 200°C; S8.3: Keep warm for 2 hours; S8.3.1: Fill with inert gas at a pressure of 0.05 MPa; S8.3.2: After holding for 30 min, apply vacuum; S8.3.3: Maintain under vacuum for 30 min; S8.3.4: Repeat steps S8.3.1-S8.3.3 once more; S8.4: Raise the temperature to 560°C; S8.5: Keep warm for 2 hours; S8.5.1: Fill with inert gas at a pressure of 0.05 MPa; S8.5.2: After holding for 30 min, apply vacuum; S8.5.3: Maintain under vacuum for 30 min; S8.5.4: Repeat steps S8.5.1-S8.5.3 once more; S8.6: Raise the temperature to 820°C; S8.7: Keep warm for 3 hours; S8.7.1: Fill with inert gas at a pressure of 0.05 MPa; S8.7.2: After holding for 30 min, apply vacuum; S8.7.3: Maintain under vacuum for 30 min; S8.7.4: Repeat steps S8.7.1-S8.7.3 two more times; S8.8: Evacuate to a vacuum degree less than 10 -2 Pa, the sintering temperature was raised to 1082°C and kept at this temperature for 7 hours; S9: After sintering, high-purity inert gas is filled in to cool down to below 100°C; S9.1: After a secondary aging treatment process at 900°C for 2-3 hours and 500°C for 3-6 hours, high-purity inert gas is filled to cool to below 100°C; S10: taking the center part of the sintered magnet, testing the nitrogen and oxygen contents in the blank by pulse infrared absorption method, and testing the carbon content in the blank by high frequency-infrared absorption method; S11: The sintered magnet is processed into a 10mm×10mm×5mm sheet, and grain boundary diffusion is performed by printing. The diffusion source is pure Tb, and the weight gain ratio is 0.62wt%; S12: The magnetic properties before and after diffusion are tested using a NIM62000 magnetic tester.

[0022] Example 1.2: The casting formula is: (PrNd) 30% B 0.94% Ti 0.2% (Al + Cu + Ga) 0.35% Co 1%, and the rest is Fe.

[0023] The steps are as follows: S1: Mix NdFeB raw materials in proportion; S2: Smelting the NdFeB raw materials into alloy liquid; S3: Casting the alloy liquid into casting sheets; S4: Grind the casting flakes into powder, put them into a tank with inert gas protection, and stir them thoroughly; S4.1: Add powder modifier at a ratio of 0.1wt% and stir thoroughly; S5: Pressing the powder into a green compact and orienting the green compact; S5.1: During the molding process, a release agent is sprayed in, with a weight ratio of 0.1wt%; S6: vacuum packaging; S7: performing water isostatic pressing; S8: Sintering and film stripping are performed, and the sintering adopts a multi-stage heat preservation and heating form; S8.1: Start heating from room temperature; S8.2: Raise the temperature to 200°C; S8.3: Keep warm for 3 hours; S8.3.1: Fill with inert gas at a pressure of 0.05 MPa; S8.3.2: After holding for 30 min, apply vacuum; S8.3.3: Maintain under vacuum for 30 min; S8.3.4: Repeat steps S8.3.1-S8.3.3 two more times; S8.4: Raise the temperature to 560°C; S8.5: Keep warm for 3 hours; S8.5.1: Fill with inert gas at a pressure of 0.05 MPa; S8.5.2: After holding for 30 min, apply vacuum; S8.5.3: Maintain under vacuum for 30 min; S8.5.4: Repeat steps S8.5.1-S8.5.3 two more times; S8.6: Raise the temperature to 820°C; S8.7: Keep warm for 4 hours; S8.7.1: Fill with inert gas at a pressure of 0.05 MPa; S8.7.2: After holding for 30 min, apply vacuum; S8.7.3: Maintain under vacuum for 30 min; S8.7.4: Repeat steps S8.7.1-S8.7.3 three more times; S8.8: Evacuate to a vacuum degree less than 10 -2 Pa, the sintering temperature was raised to 1082°C and kept at this temperature for 7 hours; S9: After sintering, high-purity inert gas is filled in to cool down to below 100°C; S9.1: After a secondary aging treatment process at 900°C for 2-3 hours and 500°C for 3-6 hours, high-purity inert gas is filled to cool to below 100°C; S10: taking the center part of the sintered magnet, testing the nitrogen and oxygen contents in the blank by pulse infrared absorption method, and testing the carbon content in the blank by high frequency-infrared absorption method; S11: The sintered magnet is processed into a 10mm×10mm×5mm sheet, and grain boundary diffusion is performed by printing. The diffusion source is pure Tb, and the weight gain ratio is 0.62wt%; S12: The magnetic properties before and after diffusion are tested using a NIM62000 magnetic tester.

[0024] Comparative Example 1: The casting formula is: (PrNd) 30% B 0.94% Ti 0.2% (Al + Cu + Ga) 0.35% Co 1%, and the rest is Fe.

[0025] The steps are as follows: S1: Mix NdFeB raw materials in proportion; S2: Smelting the NdFeB raw materials into alloy liquid; S3: Casting the alloy liquid into casting sheets; S4: Grind the casting flakes into powder, put them into a tank with inert gas protection, and stir them thoroughly; S4.1: Add powder modifier at a ratio of 0.1wt% and stir thoroughly; S5: Pressing the powder into a green compact and orienting the green compact; S5.1: During the molding process, a release agent is sprayed in, with a weight ratio of 0.1wt%; S6: vacuum packaging; S7: performing water isostatic pressing; S8: Sintering and film stripping are performed, and the sintering adopts a multi-stage heat preservation and heating form; S8.1: Start heating from room temperature; S8.2: Raise the temperature to 200°C; S8.3: Keep warm for 3 hours; S8.4: Raise the temperature to 560°C; S8.5: Keep warm for 3 hours; S8.6: Raise the temperature to 820°C; S8.7: Keep warm for 4 hours; S8.8: The sintering temperature is raised to 1082°C and kept at this temperature for 7 hours; S9: After sintering, high-purity inert gas is filled in to cool down to below 100°C; S9.1: After a secondary aging treatment process at 900°C for 2-3 hours and 500°C for 3-6 hours, high-purity inert gas is filled to cool to below 100°C; S10: taking the center part of the sintered magnet, testing the nitrogen and oxygen contents in the blank by pulse infrared absorption method, and testing the carbon content in the blank by high frequency-infrared absorption method; S11: The sintered magnet is processed into a 10mm×10mm×5mm sheet, and grain boundary diffusion is performed by printing. The diffusion source is pure Tb, and the weight gain ratio is 0.62wt%; S12: The magnetic properties before and after diffusion are tested using a NIM62000 magnetic tester.

[0026] Example 2.1: The casting formula is: (PrNd) 28.5% Gd 2.5% B 0.95% Ti 0.2% (Al + Cu + Ga) 0.5% Co 0.8%, and the rest is Fe.

[0027] The steps are as follows: S1: Mix NdFeB raw materials in proportion; S2: Smelting the NdFeB raw materials into alloy liquid; S3: Casting the alloy liquid into casting sheets; S4: Grind the casting flakes into powder, put them into a tank protected by inert gas, and stir them thoroughly; S4.1: Add powder modifier at a ratio of 0.08wt% and stir thoroughly; S5: Pressing the powder into a green compact and orienting the green compact; S5.1: During the molding process, the mold release agent is sprayed in, with a weight ratio of 0.075wt%; S6: vacuum packaging; S7: performing water isostatic pressing; S8: Sintering and film stripping are performed, and the sintering adopts a multi-stage heat preservation and heating form; S8.1: Start heating from room temperature; S8.2: Raise the temperature to 200°C; S8.3: Keep warm for 2 hours; S8.3.1: Fill with inert gas at a pressure of 0.05 MPa; S8.3.2: After holding for 30 min, apply vacuum; S8.3.3: Maintain under vacuum for 30 min; S8.3.4: Repeat steps S8.3.1-S8.3.3 once more; S8.4: Raise the temperature to 560°C; S8.5: Keep warm for 2 hours; S8.5.1: Fill with inert gas at a pressure of 0.05 MPa; S8.5.2: After holding for 30 min, apply vacuum; S8.5.3: Maintain under vacuum for 30 min; S8.5.4: Repeat steps S8.5.1-S8.5.3 once more; S8.6: Raise the temperature to 820°C; S8.7: Keep warm for 3 hours; S8.7.1: Fill with inert gas at a pressure of 0.05 MPa; S8.7.2: After holding for 30 min, apply vacuum; S8.7.3: Maintain under vacuum for 30 min; S8.7.4: Repeat steps S8.7.1-S8.7.3 two more times; S8.8: Evacuate to a vacuum degree less than 10 -2 Pa, the sintering temperature was raised to 1076°C and kept at this temperature for 5 hours; S9: After sintering, high-purity inert gas is filled in to cool down to below 100°C; S9.1: After a secondary aging treatment process at 900°C for 2-3 hours and 500°C for 3-6 hours, high-purity inert gas is filled to cool to below 100°C; S10: taking the center part of the sintered magnet, testing the nitrogen and oxygen contents in the blank by pulse infrared absorption method, and testing the carbon content in the blank by high frequency-infrared absorption method; S11: The sintered magnet is processed into a 10mm×10mm×5mm sheet, and grain boundary diffusion is performed by printing. The diffusion source is pure Tb, and the weight gain ratio is 0.56wt%; S12: The magnetic properties before and after diffusion are tested using a NIM62000 magnetic tester.

[0028] Example 2.2: The casting formula is: (PrNd) 28.5% Gd 2.5% B 0.95% Ti 0.2% (Al + Cu + Ga) 0.5% Co 0.8%, and the rest is Fe.

[0029] The steps are as follows: S1: Mix NdFeB raw materials in proportion; S2: Smelting the NdFeB raw materials into alloy liquid; S3: Casting the alloy liquid into casting sheets; S4: Grind the casting flakes into powder, put them into a tank with inert gas protection, and stir them thoroughly; S4.1: Add powder modifier at a ratio of 0.08wt% and stir thoroughly; S5: Pressing the powder into a green compact and orienting the green compact; S5.1: During the molding process, the mold release agent is sprayed in, with a weight ratio of 0.075wt%; S6: vacuum packaging; S7: performing water isostatic pressing; S8: Sintering and film stripping are performed, and the sintering adopts a multi-stage heat preservation and heating form; S8.1: Start heating from room temperature; S8.2: Raise the temperature to 200°C; S8.3: Keep warm for 3 hours; S8.3.1: Fill with inert gas at a pressure of 0.05 MPa; S8.3.2: After holding for 30 min, apply vacuum; S8.3.3: Maintain under vacuum for 30 min; S8.3.4: Repeat steps S8.3.1-S8.3.3 two more times; S8.4: Raise the temperature to 560°C; S8.5: Keep warm for 3 hours; S8.5.1: Fill with inert gas at a pressure of 0.05 MPa; S8.5.2: After holding for 30 min, apply vacuum; S8.5.3: Maintain under vacuum for 30 min; S8.5.4: Repeat steps S8.5.1-S8.5.3 two more times; S8.6: Raise the temperature to 820°C; S8.7: Keep warm for 4 hours; S8.7.1: Fill with inert gas at a pressure of 0.05 MPa; S8.7.2: After holding for 30 min, apply vacuum; S8.7.3: Maintain under vacuum for 30 min; S8.7.4: Repeat steps S8.7.1-S8.7.3 three more times; S8.8: Evacuate to a vacuum degree less than 10 -2Pa, the sintering temperature was raised to 1076°C and kept at this temperature for 5 hours; S9: After sintering, high-purity inert gas is filled in to cool down to below 100°C; S9.1: After a secondary aging treatment process at 900°C for 2-3 hours and 500°C for 3-6 hours, high-purity inert gas is filled to cool to below 100°C; S10: taking the center part of the sintered magnet, testing the nitrogen and oxygen contents in the blank by pulse infrared absorption method, and testing the carbon content in the blank by high frequency-infrared absorption method; S11: The sintered magnet is processed into a 10mm×10mm×5mm sheet, and grain boundary diffusion is performed by printing. The diffusion source is pure Tb, and the weight gain ratio is 0.56wt%; S12: The magnetic properties before and after diffusion are tested using a NIM62000 magnetic tester.

[0030] Comparative Example 2: The casting formula is: (PrNd) 28.5% Gd 2.5% B 0.95% Ti 0.2% (Al + Cu + Ga) 0.5% Co 0.8%, and the rest is Fe.

[0031] The steps are as follows: S1: Mix NdFeB raw materials in proportion; S2: Smelting the NdFeB raw materials into alloy liquid; S3: Casting the alloy liquid into casting sheets; S4: Grind the casting flakes into powder, put them into a tank protected by inert gas, and stir them thoroughly; S4.1: Add powder modifier at a ratio of 0.08wt% and stir thoroughly; S5: Pressing the powder into a green compact and orienting the green compact; S5.1: During the molding process, the mold release agent is sprayed in, with a weight ratio of 0.075wt%; S6: vacuum packaging; S7: performing water isostatic pressing; S8: Sintering and film stripping are performed, and the sintering adopts a multi-stage heat preservation and heating form; S8.1: Start heating from room temperature; S8.2: Raise the temperature to 200°C; S8.3: Keep warm for 3 hours; S8.4: Raise the temperature to 560°C; S8.5: Keep warm for 3 hours; S8.6: Raise the temperature to 820°C; S8.7: Keep warm for 4 hours; S8.8: The sintering temperature is raised to 1076°C and kept at this temperature for 5 hours; S9: After sintering, high-purity inert gas is filled in to cool down to below 100°C; S9.1: After a secondary aging treatment process at 900°C for 2-3 hours and 500°C for 3-6 hours, high-purity inert gas is filled to cool to below 100°C; S10: taking the center part of the sintered magnet, testing the nitrogen and oxygen contents in the blank by pulse infrared absorption method, and testing the carbon content in the blank by high frequency-infrared absorption method; S11: The sintered magnet is processed into a 10mmx10mmx5mm sheet, and grain boundary diffusion is performed by printing. The diffusion source is pure Tb, and the weight gain ratio is 0.56wt%; S12: The magnetic properties before and after diffusion are tested using a NIM62000 magnetic tester.

[0032] Example 3.1: The casting formula is: (PrNd) 28.8% (Dy+Gd) 2.1% B 0.95% Ti 0.2% (Al+Cu+Ga) 1.0% Co 0.5%, and the rest is Fe.

[0033] The steps are as follows: S1: Mix NdFeB raw materials in proportion; S2: Smelting the NdFeB raw materials into alloy liquid; S3: Casting the alloy liquid into casting sheets; S4: Grind the casting flakes into powder, put them into a tank protected by inert gas, and stir them thoroughly; S4.1: Add powder modifier at a ratio of 0.08wt% and stir thoroughly; S5: Pressing the powder into a green compact and orienting the green compact; S5.1: During the molding process, the mold release agent is sprayed in, with a weight ratio of 0.075wt%; S6: vacuum packaging; S7: performing water isostatic pressing; S8: Sintering and film stripping are performed, and the sintering adopts a multi-stage heat preservation and heating form; S8.1: Start heating from room temperature; S8.2: Raise the temperature to 200°C; S8.3: Keep warm for 2 hours; S8.3.1: Fill with inert gas at a pressure of 0.05 MPa; S8.3.2: After holding for 30 min, apply vacuum; S8.3.3: Maintain under vacuum for 30 min; S8.3.4: Repeat steps S8.3.1-S8.3.3 once more; S8.4: Raise the temperature to 560°C; S8.5: Keep warm for 2 hours; S8.5.1: Fill with inert gas at a pressure of 0.05 MPa; S8.5.2: After holding for 30 min, apply vacuum; S8.5.3: Maintain under vacuum for 30 min; S8.5.4: Repeat steps S8.5.1-S8.5.3 once more; S8.6: Raise the temperature to 820°C; S8.7: Keep warm for 3 hours; S8.7.1: Fill with inert gas at a pressure of 0.05 MPa; S8.7.2: After holding for 30 min, apply vacuum; S8.7.3: Maintain under vacuum for 30 min; S8.7.4: Repeat steps S8.7.1-S8.7.3 two more times; S8.8: Evacuate to a vacuum degree less than 10 -2 Pa, the sintering temperature was raised to 1073°C and kept at this temperature for 5 hours; S9: After sintering, high-purity inert gas is filled in to cool down to below 100°C; S9.1: After a secondary aging treatment process at 900°C for 2-3 hours and 500°C for 3-6 hours, high-purity inert gas is filled to cool to below 100°C; S10: taking the center part of the sintered magnet, testing the nitrogen and oxygen contents in the blank by pulse infrared absorption method, and testing the carbon content in the blank by high frequency-infrared absorption method; S11: The sintered magnet is processed into a 10mm×10mm×5mm sheet, and then subjected to grain boundary diffusion by printing. The diffusion source is pure Tb, and the weight gain ratio is 0.65wt%; S12: The magnetic properties before and after diffusion are tested using a NIM62000 magnetic tester.

[0034] Example 3.2: The casting formula is: (PrNd) 28.8% (Dy+Gd) 2.1% B 0.95% Ti 0.2% (Al+Cu+Ga) 1.0% Co 0.5%, and the rest is Fe.

[0035] The steps are as follows: S1: Mix NdFeB raw materials in proportion; S2: Smelting the NdFeB raw materials into alloy liquid; S3: Casting the alloy liquid into casting sheets; S4: Grind the casting flakes into powder, put them into a tank with inert gas protection, and stir them thoroughly; S4.1: Add powder modifier at a ratio of 0.08wt% and stir thoroughly; S5: Pressing the powder into a green compact and orienting the green compact; S5.1: During the molding process, the mold release agent is sprayed in, with a weight ratio of 0.075wt%; S6: vacuum packaging; S7: performing water isostatic pressing; S8: Sintering and film stripping are performed, and the sintering adopts a multi-stage heat preservation and heating form; S8.1: Start heating from room temperature; S8.2: Raise the temperature to 200°C; S8.3: Keep warm for 3 hours; S8.3.1: Fill with inert gas at a pressure of 0.05 MPa; S8.3.2: After holding for 30 min, apply vacuum; S8.3.3: Maintain under vacuum for 30 min; S8.3.4: Repeat steps S8.3.1-S8.3.3 two more times; S8.4: Raise the temperature to 560°C; S8.5: Keep warm for 3 hours; S8.5.1: Fill with inert gas at a pressure of 0.05 MPa; S8.5.2: After holding for 30 min, apply vacuum; S8.5.3: Maintain under vacuum for 30 min; S8.5.4: Repeat steps S8.5.1-S8.5.3 two more times; S8.6: Raise the temperature to 820°C; S8.7: Keep warm for 4 hours; S8.7.1: Fill with inert gas at a pressure of 0.05 MPa; S8.7.2: After holding for 30 min, apply vacuum; S8.7.3: Maintain under vacuum for 30 min; S8.7.4: Repeat steps S8.7.1-S8.7.3 three more times; S8.8: Evacuate to a vacuum degree less than 10 -2 Pa, the sintering temperature was raised to 1073°C and kept at this temperature for 5 hours; S9: After sintering, high-purity inert gas is filled in to cool down to below 100°C; S9.1: After a secondary aging treatment process at 900°C for 2-3 hours and 500°C for 3-6 hours, high-purity inert gas is filled to cool to below 100°C; S10: taking the center part of the sintered magnet, testing the nitrogen and oxygen contents in the blank by pulse infrared absorption method, and testing the carbon content in the blank by high frequency-infrared absorption method; S11: The sintered magnet is processed into a 10mm×10mm×5mm sheet, and then subjected to grain boundary diffusion by printing. The diffusion source is pure Tb, and the weight gain ratio is 0.65wt%; S12: The magnetic properties before and after diffusion are tested using a NIM62000 magnetic tester.

[0036] Comparative Example 3: The casting formula is: (PrNd) 28.8% (Dy+Gd) 2.1% B 0.95% Ti 0.2% (Al+Cu+Ga) 1.0% Co 0.5%, and the rest is Fe.

[0037] The steps are as follows: S1: Mix NdFeB raw materials in proportion; S2: Smelting the NdFeB raw materials into alloy liquid; S3: Casting the alloy liquid into casting sheets; S4: Grind the casting flakes into powder, put them into a tank with inert gas protection, and stir them thoroughly; S4.1: Add powder modifier at a ratio of 0.08wt% and stir thoroughly; S5: Pressing the powder into a green compact and orienting the green compact; S5.1: During the molding process, the mold release agent is sprayed in, with a weight ratio of 0.075wt%; S6: vacuum packaging; S7: performing water isostatic pressing; S8: Sintering and film stripping are performed, and the sintering adopts a multi-stage heat preservation and heating form; S8.1: Start heating from room temperature; S8.2: Raise the temperature to 200°C; S8.3: Keep warm for 3 hours; S8.4: Raise the temperature to 560°C; S8.5: Keep warm for 3 hours; S8.6: Raise the temperature to 820°C; S8.7: Keep warm for 4 hours; S8.8: The sintering temperature is raised to 1073°C and kept at this temperature for 5 hours; S9: After sintering, high-purity inert gas is filled in to cool down to below 100°C; S9.1: After a secondary aging treatment process at 900°C for 2-3 hours and 500°C for 3-6 hours, high-purity inert gas is filled to cool to below 100°C; S10: taking the center part of the sintered magnet, testing the nitrogen and oxygen contents in the blank by pulse infrared absorption method, and testing the carbon content in the blank by high frequency-infrared absorption method; S11: The sintered magnet is processed into a 10mmx10mmx5mm sheet, and grain boundary diffusion is performed by printing. The diffusion source is pure Tb, and the weight gain ratio is 0.65wt%; S12: The magnetic properties before and after diffusion are tested using a NIM62000 magnetic tester.

[0038] The above-mentioned pulse infrared absorption method and high-frequency-infrared absorption method are both conventional testing methods.

[0039] like Figure 1 As shown, the figure shows the sintering curves and the sintering equipment pressure change curves in the sintering equipment of Example 1.2, Example 2.2, and Example 3.2.

[0040] Table 1 Carbon and oxygen contents in the center of the magnet blank in each embodiment and comparative example Table 2 Magnetic properties and coercive force increase before and after diffusion of each embodiment and comparative example Magnets processed through a NdFeB sintering method that facilitates decarburization have the following improvements: 1. From Table 1, it can be seen that among the same type of NdFeB magnets, the carbon and oxygen contents of the magnets that have been repeatedly filled with inert gas and evacuated will drop significantly.

[0041] 2. From Table 2, it can be seen that among the same type of NdFeB magnets, the magnets that have been repeatedly filled with inert gas and evacuated have a higher H CJ It has been improved and the magnetic properties of the magnet are better.

[0042] By adopting a multi-stage heating and insulation platform during sintering, and introducing and withdrawing inert gas during insulation to form an inert gas pressure difference for alternate insulation sintering, the carbon content inside the billet can be effectively reduced, thereby reducing the blockage of carbon elements to grain boundary diffusion, increasing the diffusion range of grain boundary diffusion, and thus improving the magnetic properties of iron boron magnets.

[0043] The above description is only for the best embodiment of the present invention, but it should not be understood as limiting the claims. The present invention is not limited to the above embodiments, and its specific structure is allowed to be changed. All changes made within the scope of protection of the independent claims of the present invention are within the scope of protection of the present invention.

Claims

1. A sintering method of NdFeB magnets that helps decarburization. The chemical formula of NdFeB magnets is R X1 T (100-X1-X2-X3-X4) M X3 A X4 B X2 , characterized in that, During sintering, a multi-stage heating and insulation platform is used, and during insulation, inert gas is introduced and extracted to form an inert gas pressure difference for alternating insulation sintering, thereby reducing the carbon content inside the blank. The main steps are as follows: S1: Mix NdFeB raw materials in proportion; S2: Smelting the NdFeB raw materials into alloy liquid; S3: Casting the alloy liquid into casting sheets; S4: Grind the casting flakes into powder, put them into a tank with inert gas protection, and stir them thoroughly; S5: Pressing the powder into a green compact and orienting the green compact; S6: vacuum packaging; S7: performing water isostatic pressing; S8: Sintering and film stripping are performed. The sintering adopts a multi-stage heat preservation and temperature rise form, and inert gas is introduced and extracted during the heat preservation to form an inert gas pressure difference for alternating heat preservation and sintering; S9: After sintering, cool to below 100°C; S10: Take the center part of the sintered magnet and test the nitrogen and oxygen contents in the blank by pulse infrared absorption method, and test the carbon content in the blank by high-frequency-infrared absorption method.

2. A NdFeB sintering method that helps decarburization according to claim 1, characterized in that: In step S8, the following steps are included: S8.1: Start heating from room temperature; S8.2: Raise the temperature to 100°C~400°C; S8.3: Keep warm for 1h~4h; S8.4: Raise the temperature to 400°C~600°C; S8.5: Keep warm for 1h~4h; S8.6: Raise the temperature to 600°C~900°C; S8.7: Keep warm for 1h~4h.

3. A NdFeB sintering method that helps decarburization according to claim 2, characterized in that: In steps S8.3, S8.5, and S8.7, The following steps are involved: A1: After starting to keep warm, fill with inert gas; A2: After keeping it for a while, vacuumize it; A3: After maintaining the vacuum state for a period of time; A4: Repeat steps A1-A3 at least once.

4. A NdFeB sintering method that helps decarburization according to claim 3, characterized in that: After step S8.7, the method further includes the following steps: S8.8: Evacuate to a vacuum degree less than 10 -2 Pa, the sintering temperature is raised to 1050±50℃ and the insulation time is 4 to 15 hours.

5. A NdFeB sintering method that helps decarburization according to claim 4, characterized in that: In step S9, after sintering is completed, high-purity inert gas is filled in to cool to below 100°C.

6. A NdFeB sintering method that helps decarburization according to claim 1, characterized in that: After step S9, the method further includes step S9.1: performing aging treatment on the sintered magnet.

7. A NdFeB sintering method that facilitates decarburization according to claim 1, characterized in that: In step S4, the step S4.1 is included: adding a powder modifier in a proportion of 0.05wt%-0.5wt% and stirring the mixture thoroughly.

8. A NdFeB sintering method that facilitates decarburization according to claim 1, characterized in that: In step S5, the step S5.1 is included: spraying a release agent during the orientation molding process.

9. A NdFeB sintering method that facilitates decarburization according to claim 1, characterized in that: The following steps are also included: S11: processing the sintered magnet into thin sheets and performing grain boundary diffusion; S12: Use a magnetic tester to test the magnetic properties before and after diffusion.

Citation Information

Patent Citations

  • Sintering technology of NdFeB (neodymium iron boron) magnet

    CN103357872A

  • Method for firing low-cobalt fine-grain hard alloy by using ordinary sintering furnace

    CN105127419A

  • Degassing method for producing sintered neodymium-iron-boron

    CN106399731A

  • Sintering method for reducing carbon content of NdFeB magnet

    CN106601459A

  • Sintering process for neodymium iron boron

    CN107369511A